Analysis Of The Influence Of Legal Aspects, The Role Of The Midwife And The Rights Of Children On The Practice Of Exclusive Breast Feeding In Hutabagot Health Center, Hutabagot District, Mandailing Natal District Year 2020 - Rosmani Sinaga (Science Midwifery, 2020)
The level of health development of a country is reflected in the infant and child mortality rates. According to the Central Statistics Agency (2020) infant mortality under the age of five in Indonesia has reached 28,158 people. Of that number, 20,266 toddlers (71.97%) died in the age range 0-28 days (neonatal). A total of 5,386 toddlers (19.13%) died within the age range of 29 days - 11 months (post neonatal). Meanwhile, 2,506 toddlers (8.9%) died in the age range of 12-59 months. The most post-Natal toddler deaths were due to pneumonia, namely 14.5%, diarrhea by 9.8%, other congenital abnormalities o.5%, neurological diseases 0.9% and other factors 73.9%. Meanwhile, 42.83% of under-five deaths in the age range of 12-59 months were due to parasitic infections, 5.05% pneumonia, 4.5% diarrhea and 47.41% other factors. In order to prevent under-five deaths, comprehensive and continuous child health efforts are needed, one of which is exclusive breastfeeding (Central Bureau of Statistics and Ministry of Health, 2020). Breast milk is an important source of nutrition for babies. Breast milk is given to babies for 2 years. While exclusive breastfeeding is given to babies for 6 months without adding other food and drinks. Exclusive breastfeeding is recommended for the first six months of a baby's life. Breast milk is very necessary for the growth and development of children's intelligence. (RI Ministry of Health, 2020).